MUSLIM BROTHERHOOD AND MOROCCAN CAUSE: A READING IN THE GROUP’S MEDIA SUPPORT FOR MOROCCAN NATIONAL MOVEMENT - Fateh BOUFERROUK (Ziglôbitha)
Abstract :The role of Egyptian media in bolstering the Maghreb's efforts, notably Morocco's, played a pivotal role in advancing Morocco's national objectives. This support grew markedly as the Moroccan populace and their monarch faced increasing oppression and hostility. Egyptian journalism, characterized by its varied allegiances, steadfastly championed the Moroccan national movement. Notably, publications associated with the Muslim Brotherhood were at the forefront of this support.This article delves into how the Moroccan cause was portrayed in various publications of the Brotherhood, with a particular focus on The Muslim Brotherhood newspaper. It draws on a rich array of scholarly sources that have unearthed significant insights into the influence of the group’s media outlets in heightening awareness of the Moroccan cause and disseminating its developments to not only the Egyptian populace but also the broader Arab world. Such efforts significantly bolstered Arab solidarity with the Moroccan fight for independence.